Process intensification for high yield production of influenza H1N1 Gag virus-like particles using an inducible HEK-293 stable cell line. Issue 33 (24th July 2017) - Venereo-Sanchez, Alina; Simoneau, Melanie; Lanthier, Stéphane; Chahal, Parminder; Bourget, Lucie; Ansorge, Sven; Gilbert, Rénald; Henry, Olivier; Kamen, Amine
Highlights: Generation of inducible cell line stably expressing hemagglutinin, neuraminidase and Gag-GFP. Process optimized to increase the cell density and achieve high VLPs productivity. A 3-L perfusion bioreactor operated at 14 million cells/ml increased VLPs production by 60-fold. The 9.5 L harvest was clarified and concentrated by TFF and the VLPs were extensively characterized. Electron micrographs of VLPs final retentate revealed the expected Gag-HA-NA VLP morphology. Abstract: Influenza virus dominant antigens presentation using virus like particle (VLP) approach is attractive for the development of new generation of influenza vaccines. Mammalian cell platform offers many advantages for VLP production. However, limited attention has been paid to the processing of mammalian cell produced VLPs. Better understanding of the production system could contribute to increasing the yields and making large-scale VLP vaccine manufacturing feasible. In a previous study, we have generated a human embryonic kidney HEK-293 inducible cell line expressing Hemagglutinin (HA) and Neuraminidase (NA), which was used to produce VLPs upon transient transfection with a plasmid containing HIV-1 Gag. In this work, to streamline the production process, we have developed a new HEK-293 inducible cell line adapted to suspension growth expressing the three proteins HA, NA (H1N1 A/PR/8/1934) and the Gag fused to GFP for monitoring the VLP production. The process was optimized to reach higher volumetric yield of VLPs by increasing the cell density at the time of induction without sacrificing the cell specific productivity. A 5-fold improvement was achieved by doing media evaluation at small scale. Furthermore, a 3-L perfusion bioreactor mirrored the performance of small-scale shake flask cultures with sequential medium replacement. The cell density was increased to 14 × 10 6 cells/ml at the time of induction which augmented by 60-fold the volumetric yield to 1.54 × 10 10 Gag-GFP fluorescent events/ml, as measured by flow cytometry. The 9.5-L harvest from the perfusion bioreactor was concentrated by tangential flow filtration at low shear rate. The electron micrographs revealed the presence of VLPs of 100–150 nm with the characteristic dense core of HIV-1 particles. The developed process shows the feasibility of producing high quantity of influenza VLPs from an inducible mammalian stable cell line aiming at large scale vaccine manufacturing.